2013
DOI: 10.4314/ajpsy.v16i6.57
|View full text |Cite
|
Sign up to set email alerts
|

Screening a heterogeneous elderly South African population for cognitive impairment: the utility and performance of the Mini-Mental State Examination, Six Item Screener, Subjective Memory Rating Scale and Deterioration Cognitive Observee

Abstract: Objective: The aim of this study was to report on the prevalence of cognitive impairment, and to assess the performance and utility of subjective, objective and informant screening tools in a heterogeneous community sample. Method: A sample of 302 elderly participants (>60 years) living in residential homes in a large city in South Africa were screened for the presence of cognitive impairment using objective (Mini-Mental ) screening tools. All tools were compared to the MMSE and the influence of demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
0
16
1
Order By: Relevance
“…While all 140 of the sample had MMSE, SIS and SMCC scores, SMRS scores were only available for those who reported the presence of subjective impairment (n = 69), and DECO scores were only available for those participants who had contactable informants (n = 34) [40] . The prevalence data for dementia and MCI are reported fully in a separate paper [41] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While all 140 of the sample had MMSE, SIS and SMCC scores, SMRS scores were only available for those who reported the presence of subjective impairment (n = 69), and DECO scores were only available for those participants who had contactable informants (n = 34) [40] . The prevalence data for dementia and MCI are reported fully in a separate paper [41] .…”
Section: Resultsmentioning
confidence: 99%
“…For those participants who reported the presence of a subjective memory complaint, the SMRS [38] was also administered. If an informant was available, the informant DECO scale [39] was also administered (n = 76), with the results of this stage being reported separately elsewhere [40] .…”
Section: Methodsmentioning
confidence: 99%
“…These discrepancies could have arisen because we used education-specific cut-off values which improved the sensitivity and specificity of our tool and the variations in sociodemographic characteristics across the different study settings. In settings where the proportion of individuals with no formal education is high, it is recommended to adjust cut-offs to educational level, cultural, or age-specific factors which could influence the overall score [23, 24]. The norms developed by Crum et al [25] constitute the largest database in use with a recommended cut-off score of 19 for those with 0–4 years of education, 23 for those with 5–8 years of education, 27 for those with 9–12 years of education, and 29 for those with college education.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Christopher 16 , comparing the AD8 and SQST with the MMSE, it was determined that the sensitivity of the SQST was 74% and specificity was 77%. In another study, Ramlall et al reported that using the MMSE as the reference standard for the presence of cognitive impairment, the SQST had a sensitivity of 82.3% and specificity of 71.3% 17 . In this study, the MMSE identified 51 while the SQST identified twice the number (114) of participants with a possible cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%